The Application of Digital Twins in Precision and Ultra-precision Manufacturing - GENG Yanquan; GAO Yunli; LI Chen; YAN Yongda (Journal of Harbin University of Science and Technology)
With the rapid development of intelligent manufacturing technology, digital twin technology which serves as the physical and digital worlds, demonstrates significant application potential in the fields of precision and ultra-precision manufacturing. By creating virtual replicas of physical entities, digital twins enable real-time monitoring, prediction, and optimization of the machining process, enhancing processing accuracy and efficiency. This paper provides an overview of the current applications of digital twins in precision and ultra-precision manufacturing. It highlights the challenges that still exist in real-time data integration and high-precision modeling within digital twin technology. The paper also discusses the future development trends and potential applications of digital twins in precision and ultra-precision manufacturing.